Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error - Tedja, Milly S.; Jonas, Jost B. (Nature genetics, 2018)
Transancestral GWAS meta-analysis in 160,420 individuals identifies 139 loci associated with refractive error, including myopia. Newly identified genes implicate pathways involved in eye growth and light signaling cascades.
Gesehen am 09.05.2019